1987
DOI: 10.1080/87559128709540816
|View full text |Cite
|
Sign up to set email alerts
|

Musty/earthy aromas

Abstract: Compounds responsible for earthy and/or musty aromas in various food systems, including drinking water, are discussed. Major emphasis is given to the compounds geosmin, 2-methyl-isoborneal, and various pyrazines as contributors to both desirable and undesirable aromas. Occurrences, formation pathways, their sensory properties, and methods of analysis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 106 publications
0
36
0
Order By: Relevance
“…As lipophilic molecules, geosmin and 2-MIB are taken up rapidly through the gills and gut of fish and shellfish, causing muddy off-flavors which require prolonged depuration periods to remove. On the other hand geosmin is also responsible for the characteristic flavor in beets, and contributes to the desirable tastes in some cheeses, coffee, nuts, and vegetables (Maga, 1987;Reineccius, 1991;Lu et al, 2003). Geosmin and 2-MIB are chiral molecules, each with a (+), and a $10Â more potent (À) enantiomer.…”
Section: Terpenoids: Geosmin and 2-methylisoborneol (2-mib)mentioning
confidence: 98%
“…As lipophilic molecules, geosmin and 2-MIB are taken up rapidly through the gills and gut of fish and shellfish, causing muddy off-flavors which require prolonged depuration periods to remove. On the other hand geosmin is also responsible for the characteristic flavor in beets, and contributes to the desirable tastes in some cheeses, coffee, nuts, and vegetables (Maga, 1987;Reineccius, 1991;Lu et al, 2003). Geosmin and 2-MIB are chiral molecules, each with a (+), and a $10Â more potent (À) enantiomer.…”
Section: Terpenoids: Geosmin and 2-methylisoborneol (2-mib)mentioning
confidence: 98%
“…It is one of a few chemicals that separately or together are responsible for the characteristic earthy smell of soil (Gerber 1979). Although geosmin has some value in formulating fragrances (Escher and Morris 1981) and as a natural component of some foods (Maga 1987), in many circumstances its presence is not desirable such as when it occurs in farm-raised catfish and other aquaculture products (Howgate 2004;Tucker 2000) and drinking water (Jüttner and Watson 2007). While it can sometimes be eliminated from catfish prior to harvesting by moving the fish to clean water, this often results in harvest delays and increased costs with significant reductions in profits for farmers (Engle et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Geosmin has been isolated from soil, water, catfish, and vegetables such as dried beans or beetroot (Maga 1987). Early research revealed geosmin in Streptomyces cultures (Gerber and Lechevalier 1965) and, since then, several Streptomyces species have been found to produce geosmin under various conditions (Scho¨ller et al 2002).…”
Section: Introductionmentioning
confidence: 99%